The Use of Code Mixing by English Education Department Students during Classroom Activity - Tanjung, Faezal; Furqanul Hakim (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2021)
The research aims to find out the types of code-mixing used by English Education Department students during their presentation activity in the classroom in STKIP Paracendekia NW Sumbawa and to identify why did the students used the code-mixing. The participants of this research were 4 English Department students of STKIP Paracendekia NW Sumbawa. This research used observation, audio recording, and interview techniques in collecting the data. The result showed that there were two types of code mixing that used by English students in the presentation process, namely insertion code mixing, and alternation code mixing. Insertion code mixing was the dominant type that used by English students in the presentation process. There were 32 utterances categorized as insertion code mixing, and 9 utterances were categorized as alternation code mixing. While the reasons of student using code mixing in the presentation process were mostly because of the situation and lack of vocabulary.